Novelist as a vocation - Murakami, Haruki, 1949- (Alfred A. Knopf, 2022)
"A charmingly idiosyncratic look at writing, creativity, and the author's own novels. Haruki Murakami's myriad fans will be delighted by this unique look into the mind of a master storyteller. In this engaging book, the internationally best-selling author and famously reclusive writer shares with readers what he thinks about being a novelist; his thoughts on the role of the novel in our society; his own origins as a writer; and his musings on the sparks of creativity that inspire other writers, artists, and musicians. Readers who have long wondered where the mysterious novelist gets his ideas and what inspires his strangely surreal worlds will be fascinated by this highly personal look at the craft of writing"--